Perspectives and mechanisms for targeting ferroptosis in the treatment of hepatocellular carcinoma - Li, Lanqing; Wang, Xiaoqiang; Xu, Haiying; Liu, Xianqiong; Xu, Kang (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a novel process of regulated cell death discovered in recent years, mainly caused by intracellular lipid peroxidation. It is morphologically manifested as shrinking of mitochondria, swelling of cytoplasm and organelles, rupture of plasma membrane, and formation of double-membrane vesicles. Work done in the past five years indicates that induction of ferroptosis is a promising strategy in the treatment of hepatocellular carcinoma (HCC). System xc-/GSH/GPX4, iron metabolism, p53 and lipid peroxidation pathways are the main focus areas in ferroptosis research. In this paper, we analyze the ferroptosis-inducing drugs and experimental agents that have been used in the last five years in the treatment of HCC. We summarize four different key molecular mechanisms that induce ferroptosis, i.e., system xc-/GSH/GPX4, iron metabolism, p53 and lipid peroxidation. Finally, we outline the prognostic analysis associated with ferroptosis in HCC. The findings summarized suggest that ferroptosis induction can serve as a promising new therapeutic approach for HCC and can provide a basis for clinical diagnosis and prevention of this disease.